Estimating the Economic Impact and Assessing Owners' Knowledge and Practices of Epizootic Lymphangitis in Equine Cart Animals in Central and South Gondar Zones, Amhara Region, Ethiopia - Molla, Amsalu Misgie; Fentahun, Tewodros; Jemberu, Wudu T. (Frontiers in Veterinary Science, 2021)
Abstract Epizootic lymphangitis (EL) is a chronic, contagious, fungal disease of equids. The disease is highly prevalent in cart pulling equines of Ethiopia affecting the livelihood of the cart owning households and welfare of the cart animals. This study estimated the economic impacts of EL and assessed cart owners’ knowledge and practices related to the disease in northwest Ethiopia. A multistage cluster sampling was implemented to select cart animal owners for the study. A total of 274 cart animal owners were interviewed to collect data for the study. The average annual economic loss per cart owner was estimated at Ethiopian Birr (ETB) 8447. Of this loss the ETB 4364, 2838 and 1245 were due to mortality, working power loss, and treatment costs, respectively. When the loss was computed only for affected car owners, it was on average ETB 9835 per affected cart owner. The average annual animal level loss was estimated at ETB 6587 per cart animal. Mortality was the largest contributor of the overall economic losses. There was a statistically significant difference in average economic losses per household between study towns (P<0.05). The knowledge and practice study revealed that 51.2% of the respondents had good knowledge level (knowledge score above the mean score) of EL, but only 45.2% of the respondents had a good practice related to EL. A multivariable logistic regression analysis revealed that socio-demographic factors such as educational level and town of residence were significantly associated with EL knowledge level of the respondents (P< 0.05), and on the other hand knowledge level and residence of the respondents were significantly associated with EL practice level (P< 0.05). The study generally indicates that EL causes significant economic impact on the cart business, but cart owners had insufficient knowledge and poor control and preventive practices to combat the disease. Attention should be accorded to control the disease and reduce its impact on the livelihood of cart owners. As part of the control measure, more awareness creation about the disease and its preventive and management measures for cart owners will be very important.